2009
DOI: 10.1159/000257482
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ethanol-Induced Insulin Secretion from INS-1 and INS-1E Tumor Cell Lines

Abstract: Alcohol causes reactive hypoglycemia by attenuating the release of counter regulatory hormones, redistribution of pancreatic blood flow and direct stimulation of insulin secretion. Objective of this study was characterization of ethanol-induced insulin secretion. Signaling of ethanol- and glucose-induced insulin release from INS-1 and INS-1E cells was compared. Both cell lines responded similarly to all experimental interventions. In contrast to glucose, ethanol-induced insulin secretion was not hindered in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
3
5
0
Order By: Relevance
“…Our result is in agreement with previous studies performed in humans (Boden et al, 1993) and rat islets (Singh et al, 1980). However, enhancement of insulin concentration by ethanol was also observed in rat serum (Huang and Sjoholm, 2008) and in the culture media of INS-1 cells (Hafko et al, 2009). These controversial data may be due to various research conditions.…”
Section: Ethanol Overindulgence Acutely Alters Glucose Metabolismsupporting
confidence: 93%
“…Our result is in agreement with previous studies performed in humans (Boden et al, 1993) and rat islets (Singh et al, 1980). However, enhancement of insulin concentration by ethanol was also observed in rat serum (Huang and Sjoholm, 2008) and in the culture media of INS-1 cells (Hafko et al, 2009). These controversial data may be due to various research conditions.…”
Section: Ethanol Overindulgence Acutely Alters Glucose Metabolismsupporting
confidence: 93%
“…ZnCl 2 was shown to be effective inhibitor of dephosphorylation of phosphotyrosyl residues [84] and affecting exocytosis by similar mechanism as NEM. Essentially the same results received with ZnCl 2 as with NEM [83] strengthen our hypothesis that an extra pool of secretory vesicles is available for exocytosis in this type of stimulation.…”
Section: N-ethylmaleimide-sensitive-factor (Nsf) and Soluble Nsf-attasupporting
confidence: 85%
“…This response to stimulation suggests the presence of a separate pool of secretory granules available for swelling-induced but not glucose-induced exocytosis after treatment. Interestingly, high insulin secretion from NEM treated cells further increased also after ethanol stimulation [83] suggesting similar pathway for permeant effect. ZnCl 2 was shown to be effective inhibitor of dephosphorylation of phosphotyrosyl residues [84] and affecting exocytosis by similar mechanism as NEM.…”
Section: N-ethylmaleimide-sensitive-factor (Nsf) and Soluble Nsf-attamentioning
confidence: 67%
See 1 more Smart Citation
“…Recently Madsen et al [22] found that calcineurin and calcium/calmodulin suppress exocytosis of renin from juxtaglomerular cells independent of PKA. It is of interest that ethanol effect which in many aspects shares common mechanisms and properties with hypotonic stimulation [18,23,24] on insulin secretion from INS-1E cell line is not hindered by the presence of calcium [25]. It is likely that swelling and secretion-inducing effect of various permeants utilizes different pathways.…”
Section: Discussionmentioning
confidence: 99%